THE EFFECT OF POWER STRATEGY ON SENIOR HIGH SCHOOL STUDENTS’ EXPLANATION TEXT WRITING ABILITY AT SMAN 1 UKUI - Mutiara Amalia Nuril; M.Syarfi M.Syarfi; Masyhur Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: Writing is one of the basic skill that must be mastered by students or learners to comprehend English. However, it is difficult to do for some reason. The Objectives of this research are (1) to find out whether there is an effect of POWER Strategy on third-year senior high school students’ explanation text writing ability or not and (2) to find out whether there is any significant difference on the third-year senior high school students’ explanation text writing ability between those who are taught using POWER Strategy and those who are not. This research used a quantitative approach and the research design is quasi-experimental with 58 students as the sample. The samples of this research were XII MIPA 1 as Experiment Group and XII IPS 1 as Control Group, selected by using cluster random sampling. The instrument of the data collection is a written test, the data was analyzed by using SPSS 26.The results of this research were (1) there is an effect of POWER Strategy on third-year senior high school students’ explanation text writing ability proved by the result of Independent Sample T-Test, which is the significant two-tailed is 0.000 lower than Alpha 0.05 and Ha (1) is accepted. (2) there is a difference on the third-year senior high school students’ explanation text writing ability between experiment group and control group but the difference is not significant because the results of the mean score for both groups are still in the same range of mean score (Good). This is proved by the mean score of the experiment group’s post-test (74.79) is higher than the mean score of the control group’s post-test (71.17).Key Words: POWER Strategy, Writing Ability, Explanation Text.